The Influence of the Teacher Performance Appraisal System and Principal Leadership on the Quality of Teacher Performance at TK Tunas Harapan Nusa - Krisnasari, Shita; Imamah, Nuril (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study aims to investigate the effect of teacher performance appraisal and principal leadership on the quality of teacher performance in Tunas Harapan Nusa Kindergarten (TK) in West Manokwari District. This research uses field research, with quantitative research using a correlational approach. The instrument used is a questionnaire. In this study, the population and saturated samples taken were all teachers at Tunas Harapan Nusa Kindergarten, which had a population of 12 people and were used as saturated samples in this study. Quantitative data analysis using IBM SPSS Statistics 22 Based on the results, the probability number in the significance level is 0.00, where the significance level α = 0.05, then H0 is rejected and Ha is accepted. This shows that there is an influence of teacher performance appraisal and principal leadership on the quality of teacher performance at Tunas Hrapan Nusa Kindergarten in West Manokwari District. The coefficient of determination in the regression model with an adjusted R2 value of 0.751 means that 75.1 percent of the quality of teacher performance can be explained by teacher performance appraisal and principal leadership.